Design laminated bamboo side table with 50 degree of curvature leg/ Syuwari Husin - Husin, Syuwari (2014)
This study to discuss about new design of side table made from laminated bamboo board. This design use bamboo laminated board can save the manufacturing cost compare with solid wood, use bamboo as a material is to increase product in the market and uses a bamboo can save the ecosystem by just harvesting bamboo instead of cut a tree. Other than that, this study also to identifying the suitability of the design side table with a 50 degree id curvature leg.